Kinship and exchange relations within an estate economy : Ditchley, 1680-1750 - Hann, AG (1999)
This thesis presents original evidence on changes occurring within the exchange economy of a north-west Oxfordshire rural community during the first half of the eighteenth century. It has been suggested that capitalism began to evolve in rural areas of England during this period due to the transformation of agriculture and growth of consumerism. Thus one would expect to find evidence of a growing commercialisation of the agrarian population characterised by increased reliance upon the market and a diminution of customary exchange and self-provisioning. Drawing evidence from the Ditchley estate accounts, the balance of monetary and nonmonetary exchange, the nature of transactions, and the role of kinship connections in mediating them, are described and analysed. It is argued that whilst the accounts do reveal significant levels of monetization and widespread use of market exchange especially after 1725, an extensive, largely non-monetized internal estate market in goods operated in parallel. These two systems appear to have been as much complementary as in competition, reflecting the high levels of integration within the local agrarian economy of the stonebrash region. Moreover, analysis of kinship networks suggests that many seemingly monetary transactions had a social component. Market exchange at Ditchley was essentially as dependent on social relations as reciprocal exchange within the neighbourhood area. The customary economy of kinsman and neighbour continued to flourish and to complement the expanding market economy in early eighteenth-century England, because both had a moral component. For the villagers at Ditchley there was no clear dichotomy between the two.